2010
DOI: 10.1007/s12264-010-0818-2
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline reduces astrocytic reactivation and neuroinflammation in the hippocampus of a vascular cognitive impairment rat model

Abstract: Objective To study the neuroprotective mechanism of minocycline against vascular cognitive impairment after cerebral ischemia. Methods The rat model with vascular cognitive impairment was established by permanent bilateral common carotid artery occlusion (BCCAO). The observing time-points were determined at 4, 8 and 16 weeks after BCCAO.Animals were randomly divided into sham-operated group (n = 6), model group (subdivided into 3 groups: 4 weeks after BCCAO, n = 6; 8 weeks after BCCAO, n = 6; and 16 weeks afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 42 publications
2
42
0
Order By: Relevance
“…Several lines of evidence have shown that minocycline, which has anti-inflammatory and neuroprotective properties, can accelerate the recovery of cognitive functions by inhibiting astrogliosis following cerebral ischemia, mu p75-saporin immunotoxic lesioning, and onset of Alzheimer's disease [5,14,16]. Minocycline also improves cognition and memory after cognitive impairment associated with traumatic brain injury [17], early-phase schizophrenia [18], chronic cerebral hypoperfusion [19], Alzheimer's disease [6], and phencyclidine-induced cognitive deficits [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several lines of evidence have shown that minocycline, which has anti-inflammatory and neuroprotective properties, can accelerate the recovery of cognitive functions by inhibiting astrogliosis following cerebral ischemia, mu p75-saporin immunotoxic lesioning, and onset of Alzheimer's disease [5,14,16]. Minocycline also improves cognition and memory after cognitive impairment associated with traumatic brain injury [17], early-phase schizophrenia [18], chronic cerebral hypoperfusion [19], Alzheimer's disease [6], and phencyclidine-induced cognitive deficits [20].…”
Section: Discussionmentioning
confidence: 99%
“…Minocycline downregulated surgery-associated hippocampal tumor necrosis factor a, interleukin 1b, and interleukin 6 mRNA expression levels A previous study indicated that hippocampal expression levels of TNF-a and IL-1b were involved in the neuroprotective mechanism of minocycline against chronic cerebral ischemia [14]. We detected the hippocampal mRNA levels of TNF-a, IL-1b, and IL-6 using real-time PCR at the end of the experiment.…”
Section: Minocycline Inhibited Astrocytic Activation Induced By 70% Hmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, studies using experimental models of stroke also reported protective effects of minocycline on astrogliosis (Leonardo et al 2008;Cai et al 2010). Simultaneously other investigators indicated its ineffectiveness on astrogliosis and astrocytic apoptosis in stroke model indicating a complex action of this drug under same inflammatory conditions (Yrjanheikki et al 1998;Matsukawa et al 2009).…”
Section: Introductionmentioning
confidence: 92%
“…Further measures include maintaining a "normal" day-night rhythm, and maintaining the homeostasis by avoiding too long fasting before and after the procedure [7,11].Frequent visits by family and friends while the patient is still in the hospital and early discharge of patients to their own home environment also lead to a reduced incidence of POCD [7]. There are currently several studies investigating the influence of substances like dexamethason and minocycline [6].…”
Section: Postoperativelymentioning
confidence: 99%